2023
DOI: 10.1177/07482337231172816
|View full text |Cite
|
Sign up to set email alerts
|

Emission and time-resolved migration rates of aromatic diamines from two flexible polyurethane foams

Abstract: Performing risk assessments (RA) on household use of flexible polyurethane (PU) foams requires access to reliable data about emission and migration of potential diamine impurities. A toluene diisocyanate (TDI) and a methylene diphenyl diisocyanate (MDI) based foam were thermally treated to enable measurements on samples with defined concentrations of the corresponding diamines, toluene diamine (TDA), and methylene dianiline (MDA). The thermally treated foams used for emission testing contained up to 15 mg.kg−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The respective aggregate LOQ were 1.7 μg.m −2 .d −1 for each of the TDA-isomers and 3.4 μg.m −2 .d −1 for ΣMDA 1 . Migration rates matched with a theoretical model based on Fick’s diffusion law ( Karlsson et al, 2023 ; OECD, 2009 ), whereby migration rates were linear in the initial concentration of the substance and evolved with the inverse square root of time (t −0.5 ). This theoretical basis allowed for a well-founded extrapolation of the experimental data to the anticipated period of use of a mattress.…”
Section: Methodsmentioning
confidence: 59%
See 3 more Smart Citations
“…The respective aggregate LOQ were 1.7 μg.m −2 .d −1 for each of the TDA-isomers and 3.4 μg.m −2 .d −1 for ΣMDA 1 . Migration rates matched with a theoretical model based on Fick’s diffusion law ( Karlsson et al, 2023 ; OECD, 2009 ), whereby migration rates were linear in the initial concentration of the substance and evolved with the inverse square root of time (t −0.5 ). This theoretical basis allowed for a well-founded extrapolation of the experimental data to the anticipated period of use of a mattress.…”
Section: Methodsmentioning
confidence: 59%
“…The results of Karlsson et al (2023) showed that migration occurred primarily during Day 1 and that little to no replenishment of TDA and MDA from the interior to the surface of the foam took place. Average daily migration rates were calculated as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The limit of quantification (LOQ) was defined as the lowest calibration point for all analytes. By lowering the calibration range, the LOQs could be lowered further to 0.3 ng for the diisocyanates and 2,4-TDA, and to 1 ng for 2,6-TDA and MDA ( Karlsson et al, 2022a , 2022b ).…”
Section: Resultsmentioning
confidence: 99%